2004
DOI: 10.1519/1533-4287(2004)018<0129:coovtp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Olympic vs. Traditional Power Lifting Training Programs in Football Players

Abstract: Twenty members of an National Collegiate Athletic Association Division III collegiate football team were assigned to either an Olympic lifting (OL) group or power lifting (PL) group. Each group was matched by position and trained 4-days.wk(-1) for 15 weeks. Testing consisted of field tests to evaluate strength (1RM squat and bench press), 40-yard sprint, agility, vertical jump height (VJ), and vertical jump power (VJP). No significant pre- to posttraining differences were observed in 1RM bench press, 40-yard s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(122 citation statements)
references
References 22 publications
8
92
1
9
Order By: Relevance
“…Using a longitudinal approach, Hoffman et al (17) (23) this suggests that weightlifting is a more effective modality for jump training, and more generally, athletic development.…”
Section: Introductionmentioning
confidence: 99%
“…Using a longitudinal approach, Hoffman et al (17) (23) this suggests that weightlifting is a more effective modality for jump training, and more generally, athletic development.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these training methods that exist for the development and improvement of lower body power, previous research has indicated that weightlifting movements may provide a superior training stimulus [18, [21][22][23][24]. As a result, weightlifting movements such as the clean, jerk, snatch, and their derivatives (e.g., power clean, power snatch, etc.)…”
mentioning
confidence: 99%
“…Olympic lifts educate athletes on how to apply and receive force [19]. Olympic lifts also provide athletes with the ability to accelerate under different degrees of resistance.…”
mentioning
confidence: 99%